Development of an inventory management system using association rule - Tinuke Omolewa Oladele; Roseline Oluwaseun Ogundokun; Adekanmi Adeyinka Adegun; Emmanuel Abidemi Adeniyi; Ayobami Tayo Ajanaku (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Stores today still make use of manual approaches to keeping inventory which could be cumbersome. Having a computerized inventory system would make inventory management more efficient and effective. In this chapter, an Inventory Management System using Association Rule was developed which will ensure proper record keeping and keep items in stocks updated. ANGULARJS, a JavaScript framework, was used for the implementation of the system, PHP (hypertext pre-processor) was used for the backend of the system development as well as the database management, HTML was used alongside CSS for the system interface design and NoSQL database was the database used for this research. In conclusion, a computerized inventory system that had been improved using the Association Rule method was the resulting product useful for creating transactions, updating items in stock, record keeping, generating reports for decision making, and lastly, the system will make the stores more effective.